In situ construction of α-Bi2O3/g-C3N4/β-Bi2O3 composites and their highly efficient photocatalytic performances. Issue 113 (30th October 2015) - Jiang, Hai-Ying; Liu, Guigao; Wang, Tao; Li, Peng; Lin, Jun; Ye, Jinhua
Abstract : In this study, α-Bi2 O3 /g-C3 N4 /β-Bi2 O3 composites were constructed by an in situ method in one step from α-Bi2 O3 and g-C3 N4 . Abstract : In this study, α-Bi2 O3 /g-C3 N4 /β-Bi2 O3 composites were constructed by an in situ method in one step from α-Bi2 O3 and g-C3 N4 . It indicates that α-Bi2 O3 transformed to β-Bi2 O3 when it was calcined together with g-C3 N4 . The co-existence of α-Bi2 O3, g-C3 N4 and β-Bi2 O3 was proved by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy and high-resolution transmission electron microscopy (HRTEM). The energy band structures and optical properties were studied by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) and valence band X-ray photoelectron spectroscopy (VB-XPS). The in situ formation mechanism of the α-Bi2 O3 /g-C3 N4 /β-Bi2 O3 composites in one step was studied using the samples' surface chemical states, which were measured by X-ray photoelectron spectroscopy (XPS). The results show that the surface covered or coordinated g-C3 N4 and CO3 2− which has a promotional effect on the stability of β-Bi2 O3 at room temperature. The enhanced photocatalytic activities of the α-Bi2 O3 /g-C3 N4 /β-Bi2 O3 composites were evaluated by the photocatalytic oxidation of isopropyl alcohol (IPA), and were attributed to the heterojunction formation between β-Bi2 O3 and g-C3 N4 .